Expression of cytochrome P450 genes in CD34+ hematopoietic stem and progenitor cells - Soucek, Pavel; Anzenbacher, Pavel; Skoumalová, Ivana; Dvorák, Michal (Stem cells (Dayton, Ohio), 2005)
Expression of major cytochrome P450 forms (P450) was followed in preparation of purified hematopoietic CD34+ stem and progenitor cells. Levels of transcripts as well as mature proteins were traced by quantitative real-time polymerase chain reaction and by Northern and Western blotting. P450 1B1 and P450 2E1 proteins and respective mRNAs were found in all cases. On the other hand, no expression of P450 3A4, P450 3A7, and P450 2C9 was found. The results showed that expression of various P450 enzymes starts at different stages of cell differentiation. Both P450 forms found are known to be connected with cancer cells and with activation of procarcinogens (P450 1B1, polycyclic aromatic hydrocarbons; P450 2E1, nitrosamines, and solvents). Hence, cells at the early stage of differentiation already may be influenced by interaction with xenobiotics. This fact should also be taken into consideration when hematopoietic cell transplant therapy is applied.
Keywords: messenger RNA; systém (enzymů) cytochromů P-450; Cyclophilin A; průtoková cytometrie; DNA, Complementary; imunoblotting; cyklofilin A; Antigens, CD34; Cytochrome P-450 Enzyme System; RNA; Flow Cytometry; Immunoblotting; Isoenzymes; Gene Expression; komplementární DNA; RNA, Messenger; Humans; izoenzymy; exprese genu; hematopoetické kmenové buňky; antigeny CD34; Hematopoietic Stem Cells; lidé